MULTIPLIKASI ANGGREK (Dendrobium sp) DENGAN PEMBERIAN ZPT ZEATIN DAN IAA (Indole Acetic Acid) SECARA IN-VITRO - Syafiq Zulhakim; Maizar; Adelina Maryanti; Tati Maharani (DINAMIKA PERTANIAN, 2025)
The research entitled Multiplication of Orchid Dendrobium sp. by Giving GRS Zeatin and IAA (Indole Acetic Acid) In Vitro was carried out at the Biotechnology Laboratory of the Faculty of Agriculture, Islamic University of Riau, Pekanbaru City. The research was conducted over three months, from December 2022 to February 2023. This study aimed to obtain a combination of Zeatin and IAA (Indole Acetic Acid) concentrations that had the best effect on the growth of Dendrobium orchid explants in tissue culture. The design used in this study was a factorial experiment in a completely randomized design (CRD), consisting of two factors and three replications. The first factor was Zeatin (Z) at concentrations of 0, 2.0, 4.0, and 6.0 ppm, while the second factor was IAA at concentrations of 0, 0.5, 1, and 1.5 ppm. Parameters observed were explant survival (%), shoot age (days), root age (days), number of shoots (fruits), number of roots (fruits), shoot length (cm), and root length (cm). The observational data were analyzed statistically, and the BNJ follow-up test was conducted at the 5% level. The results showed that the interaction between Zeatin and IAA had a significant effect on shoot age, root age, number of shoots, number of roots, shoot length, and root length, with the best concentrations being Zeatin (6 ppm) and IAA (1 ppm). Meanwhile, the percentage of explant survival did not have a significant effect.